KURIKULUM PONDOK PESANTREN TRADISIONAL: INTEGRASI ILMU AGAMA, AKHLAK DAN KEHIDUPAN BERBASIS SANTRI - Nur Asikin (ADISAM PUBLISHER, 2026)
This study discusses the curriculum of Islamic boarding schools which integrates religious knowledge, character building, and student-based life education. The purpose of this study is to explain how these three aspects are interconnected in shaping well-rounded students. The method used is a literature study by reviewing various sources related to Islamic boarding school education. The results show that the integration of religious knowledge provides a strong foundation for students in understanding Islamic teachings. Character building is carried out through role modeling, habituation, and a religious environment, which helps form good character. Student-based life education trains independence, discipline, and social skills through daily life experiences in the boarding school environment. The conclusion indicates that the pesantren curriculum is able to produce students who are not only knowledgeable but also possess noble character and are ready to face social life.